Effectiveness of Technical Indicators in Singapore Stock Market - Zhao, Yuanyuan (2007)
In this paper I am going to evaluate the effectiveness (profitability) of technical analysis, in particular the use of indicators in combinations, in the Singapore context. I am benchmarking the annualized percentage returns on two groups of SGX-listed companies against buy-and-hold for a period of two years, as well as comparing between groups. Both would be achieved by using statistical testing.